A General Overview on Some Aspects of Fish Reproduction - Zainal A. Muchlisin (Graduate Program of Syiah Kuala University, 2014)
Abstract - Reproduction is one of the important physiological systems that are crucial in the life cycle of living organisms including fish. The main objective of the reproduction is to maintain the existence of the species and therefore fish have a strategies and tactics to achieve this objective. The reproduction behaviours are important to be studied in relation to know the population dynamic of fishes and their spawning seasons. This information is very crucial in relation to the development of breeding technology for aquaculture and conservation (restocking) purposes. This paper reviews the reproductive strategy, fecundity and spawning frequency of fishes.Keywords: Fecundity; Spawning frequency; Gonadal development; Synchronous; gonadosomoatic index